PENGEMBANGAN MIE KERING BERBASIS TEPUNG MOCAF, TEPUNG UBI JALAR UNGU, TEPUNG IKAN GABUS SEBAGAI ALTERNATIF MAKANAN SELINGAN BAGI PENDERITA DIABETES MELITUS - Fauziyah, Riska Laili; Hapsari, Agustina Indri; Moviana, Yenni (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2025)
The International Diabetes Federation in 2021 stated that diabetes mellitus patients in the world reached 537 million people and ranked third in Indonesia. Diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia due to insufficient insulin hormone production. Noodles are a snack that people like to consume, in addition to the development of snacks for people with DM, which are more sweet foods. The purpose of this study was to determine the effect of mocaf flour formulation, purple sweet potato flour, and cork fish flour on organoleptic characteristic, nutrients, and production costs of dry noodles as an alternative snack food for people with diabetes mellitus. This research design is experimental with the formulation of the ratio of mocaf flour, purple sweet potato flour and cork fish flour F1 30%:10%:8%, F2 38%:10%:10%, F3 43%:8%:12%. The samples in the organoleptic test were 20 moderately trained panelists. The results of the organoleptic test showed that there were significant differences in aroma and overall acceptance of the dry noodles produced (p<0.05) with F3 is the formula most liked by panelists with aspects of color 60% like, aroma 80% like, texture 35% like, taste 60% like, and overall 85% like. One serving size of dry noodles is 60 grams. The proximate test results showed the nutritional value/100 grams of protein 5,90 grams, fat 6,48 grams, carbohydrates 81,84 grams and fiber 1,52 grams. Further research can be done objectively testing (triplo test), conducting research on people with diabetes mellitus, as well as product development on other types of dishes. Key words: dry noodle, diabetes mellitus, mocaf flour, purple sweet potato flour, cork fish flour, organoleptic test.